Predictors of dental complications post‐dental treatment in patients with sickle cell disease - Monica Amorim Da Silva Gusmini; Anny Clementino De Sa; Changyong Feng; Szilvia Arany (Clinical and Experimental Dental Research, 2021)
Abstract Objective Our aim was to explore potential medical or dental indicators associated with dental complications and the utilization of emergency services in sickle cell disease (SCD), especially that clinical reports on adverse outcomes post‐dental treatment are scarce. Materials and methods A retrospective analysis of dental treatments of 47 eligible adults with confirmed SCD between May 2016 and October 2019. Logistic regression analysis was used whether clinical outcomes, course of dental treatment, and regularity of dental care are associated with dental complications after dental procedures and/or resulted in emergency care or hospital admissions. Results We identified a new, statistically significant association (p‐value = .01) between the number of prescription medications taken and complications (10%) after dental procedures. The most frequent dental procedures were tooth extractions (36%) and pain management (28%) during a non‐scheduled dental encounter (68%). The majority of cases did not participate in regular recall exams and periodical oral hygiene maintenance. Conclusions A higher number of prescription medications was associated with an increased risk of post‐dental complications in SCD patients. A thorough medical history, including a list of prescribed medications, and collaboration with the patient medical team are important to assess the risk of complications post‐dental procedures and the need for antibiotic prophylaxis according to the case complexity.